Theoretical Premises of the Marxist Study of Morality - Kalenda, Česlovas (Problemos, 1985)
The essence of the Marxist approach to morality as a corollary of the Marxist conception of society and man is shown. On the basis of the Marxist interpretation of genesis of consciousness the socio-practical origin of morality is revealed. Dynamic character of its relation to other social processes and the content of the principle of historicity in the study of phenomena of morality is disclosed. At the same time non-Marxist conceptions of ethics and vulgar interpretations of the Marxist conception of morality are polemized.